Organic-inorganic composite polymer solid electrolyte and preparation method and application thereof
By introducing strong alkaline amidinyl compounds into polyoxyethylene oxide (PEO) polymer organic-inorganic composite solid electrolyte, the problems of low conductivity and large interface impedance are solved, and the lithium ion conductivity and mechanical properties are improved, and the overall performance of the battery is improved.
Patent Information
- Application Number
- CN202411846460.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-16
- Publication Date
- 2025-03-21
- Estimated Expiration
- 2044-12-16
AI Technical Summary
The existing polyoxyethylene (PEO) polymer organic-inorganic composite solid electrolytes have insufficient performance, large interface impedance, and low critical current density.
Amidine compound with strong basicity is introduced to promote the peristalticity of the polymer segment and the acid-baseness inside the solid electrolyte by combining with the electron-absorbing group in the polymer group, thereby converting the fixed lithium ions into a free state, reducing the migration energy barrier of lithium ions, and improving the conductivity and mechanical properties of lithium ions.
The lithium-ion conductivity and mechanical strength of PEO-based organic-inorganic composite solid electrolyte at room temperature is significantly improved, interface stability is improved, and overall battery performance is improved.
Smart Images

Figure CN119674190A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of lithium ion batteries, and in particular to an organic-inorganic composite polymer solid electrolyte and a preparation method and application thereof. Background Art
[0002] Lithium-ion batteries are widely used in energy storage power systems such as hydropower, thermal power, wind power and solar power stations, as well as various electric vehicles, military and aerospace fields. As an important component of lithium-ion batteries, electrolytes affect and even determine a variety of macroscopic electrochemical properties of batteries, such as specific energy, life, and safety performance. At present, electrolytes have developed from liquid electrolytes to solid electrolytes. Solid electrolytes have higher chemical stability and thermal stability, which can improve the safety performance of batteries. Polymer solid electrolytes are light, flexible, highly thermally stable, and have good contact with the electrode interface, and have good application prospects. Polyethylene oxide (PEO) polymer solid electrolytes are the most widely studied polymer electrolyte system to date, and are also the most promising for large-scale production.
[0003] However, the existing polyoxyethylene (PEO) polymer organic-inorganic composite solid electrolytes have the disadvantages of low conductivity, large interface impedance, low critical current density, etc. To solve the above problems, the commonly used methods include adding inorganic active materials for modification, adding ion plastic crystals to improve its lithium ion conductivity, and constructing composite solid electrolytes.
[0004] Chinese patent document CN117352833A discloses an organic-inorganic composite polymer solid electrolyte, which adjusts its conductivity by adding different proportions of polyvinylidene fluoride (PVDF) and lithium salts in PEO, and further improves the performance of the battery by adding active fillers and fluorobenzene compounds in the PEO-based organic-inorganic composite polymer solid electrolyte, but its conductivity, battery capacity retention rate and mechanical properties are still not ideal, and fluorobenzene compounds have certain toxicity, which is not conducive to environmental protection. Chinese patent document CN116806221A discloses the preparation of an ionic plastic crystal and its application in electrolytes. The plastic crystal contains at least one delocalized anion derived from at least one cation pairing of a guanidine, amidine or phosphazene organic superbase, and the structure of the organic superbase is mainly alkane and ester groups, which has certain limitations on the improvement of lithium ion conductivity. The patent first synthesizes plastic crystals, and then uses plastic crystals to prepare organic-inorganic polymer solid electrolytes, and the preparation method is complicated. Summary of the invention
[0005] In order to solve the problems of low lithium ion conductivity, poor interface stability and poor mechanical properties of solid electrolytes, the present invention provides an organic-inorganic composite polymer solid electrolyte and its preparation method and application. The introduction of a strongly alkaline amidine group can provide a large number of electron pairs and combine with the electron-withdrawing group in the polymer group; promote the creep of the polymer segment and the acidity and alkalinity inside the solid electrolyte, thereby converting the lithium ions fixed inside the polymer solid electrolyte into a free state, greatly reducing the migration energy barrier of lithium ions inside the polymer, thereby promoting the rapid and efficient transmission of lithium ions in the PEO-based organic-inorganic composite solid electrolyte at room temperature and improving the mechanical properties.
[0006] In order to achieve the above technical objectives, the present invention adopts the following technical solutions:
[0007] An organic-inorganic composite polymer solid electrolyte comprises polyethylene oxide, a lithium salt, an active filler and an organic additive, wherein the organic additive is an amidine compound, and the amidine compound contains one or more of halogen, phenyl, nitro, naphthyl or thiophene groups; the polyethylene oxide and the lithium salt have a molar ratio of EO:Li of (4-30):1, a total mass ratio of the polyethylene oxide and the lithium salt to the active filler is (2-40):1, and a total mass ratio of the polyethylene oxide and the lithium salt to the organic additive is (1.5-15):1.
[0008] Preferably, the amidine compound includes one or more of 3,4-dimethylbenzamide, 2-(4-fluorophenylmethylsulfonyl)hydroxyacetamidine, 2-pyrazineamidine hydrochloride, N-hydroxy-6-chloroindoleacetamidine, N-[3-(aminomethyl)benzyl]acetamidine, methyl-[5-(N-methyl-N-phenylamino)-2,4-pentadienyl]phenylammonium chloride, esifamidine, pentafluoropropylamidine, N'-hydroxy-2-naphthamide, heptafluorobutyrylamidine, 2-(2-thienyl)hydroxyacetamidine, propamidine, 4-methylsulfonylbenzamide, 2-N-BOCaminoethylamidine, 4-benzylpiperazine-1-carbonamidine, and 4-nitrobenzamide.
[0009] Further preferably, the amidine compound is selected from at least one of 2-pyrazineamidine hydrochloride, N-hydroxy-6-chloroindolecarboxamidine, methyl-[5-(N-methyl-N-phenylamino)-2,4-pentadienyl]phenylammonium chloride and 4-methylsulfonylphenylamidine.
[0010] Preferably, the lithium salt includes one or more of LiFSI, LiTFSI, LiBOB, LiODFB, LiPF6, LiClO4, and LiNO3. LiODFB is further preferred. The combination of lithium salt and organic additives can effectively improve the lithium ion conductivity of the solid electrolyte and reduce the interface impedance.
[0011] Preferably, the active filler comprises lithium lanthanum zirconium tantalum oxide (Li 6.5 LqCy 1.5 Ta 0.5 O 12 ,LLZTO), lithium indium chloride (Li3InCl6), lithium aluminum titanium phosphide (Li 1.3 Al 0.3 Ti 1.7 (PO4)3, LATP), lithium aluminum germanium phosphide (Li 1.5 Al 0.5 Ge 1.5 (PO4)3, LAGP) and lithium phosphorus sulfur chlorine (Li6PS5Cl, LPSCl) One or more.
[0012] Preferably, the molar ratio of EO:Li of the polyethylene oxide and the lithium salt is (7-9):1, the mass ratio of the total mass of the polyethylene oxide and the lithium salt to the active filler is (9-11):1, and the mass ratio of the total mass of the polyethylene oxide and the lithium salt to the organic additive is (6-7):1.
[0013] The organic-inorganic composite polymer solid electrolyte provided by the present invention has ultra-high lithium ion conductivity and high mechanical strength, because: first, the strong alkalinity of the amidine group can promote the dissociation of lithium salts, thereby effectively improving the lithium ion conductivity. Second, the connecting group interacts with the dissociated lithium ions, thereby forming an interface layer with high lithium ion conductivity and high interface stability on the interface, thereby effectively improving the interface stability. Finally, the added amidine organic additive improves the bonding environment of the solid electrolyte, greatly improving the mechanical strength of the solid electrolyte.
[0014] The present invention also provides a method for preparing an organic-inorganic composite polymer solid electrolyte, comprising the following steps: weighing each component, adding an organic solvent, heating and stirring to obtain a uniformly mixed slurry, and then casting and vacuum drying to obtain a polymer solid electrolyte.
[0015] Preferably, the solid content of the slurry is 20% to 40%. Preferably, the polyoxyethylene is dried before use, the drying temperature is 20 to 180°C, and the drying time is 2 to 60 hours; more preferably, the drying temperature is 45 to 120°C, and the drying time is 2 to 24 hours.
[0016] Preferably, the organic solvent used includes one or more of acetonitrile, dimethylacetamide (DMAC), dimethyl sulfoxide (DMSO), N-methylpyrrolidone (NMP), and N,N-dimethylformamide.
[0017] Preferably, the temperature used for heating and stirring is 20 to 150°C, more preferably 20 to 80°C.
[0018] Preferably, the heating and stirring time is 8 to 60 hours, more preferably 10 to 24 hours.
[0019] Preferably, the temperature used for vacuum drying is 20 to 100°C, more preferably 60 to 100°C.
[0020] Preferably, the vacuum drying time is 2 to 48 hours, more preferably 8 to 36 hours.
[0021] The present invention also provides an application of an organic-inorganic composite polymer solid electrolyte in the preparation of a lithium electronic battery.
[0022] The present invention has the following advantages:
[0023] The present invention introduces amidine compounds with special groups (halogen, nitro, phenyl and amino, etc.) into PEO-based polymer solid electrolytes to interact with lithium salts, promote the dissociation of lithium salts, and form a high lithium ion conductivity interface of phenyl lithium and lithium nitrate rich in LiX (X = F, Cl, Br, I, etc.) on the interface, thereby improving the stability of the interface. The ionic conductivity of PEO-based organic-inorganic composite solid electrolytes at room temperature can be effectively improved (up to 8.1×10 -4 S cm -1 ). The present invention introduces an amidine group with strong alkalinity, which can provide a large number of electron pairs and combine with the electron-withdrawing group in the polymer group; promote the creeping property of the polymer chain segment and the acidity and alkalinity inside the solid electrolyte, thereby converting the lithium ions fixed inside the polymer solid electrolyte into a free state, greatly reducing the migration energy barrier of the lithium ions inside the polymer, thereby promoting the rapid and efficient transmission of lithium ions in the PEO-based organic-inorganic composite solid electrolyte at room temperature and improving the mechanical properties. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 The lithium ion conductivity diagram of the PEO-based organic-inorganic composite polymer electrolyte membrane obtained in Comparative Example 1;
[0025] Figure 2 The interfacial impedance diagram of the PEO-based organic-inorganic composite polymer electrolyte membrane obtained in Comparative Example 1;
[0026] Figure 3 This is a test diagram of the cycle performance of a full battery of the PEO-based organic-inorganic composite polymer electrolyte membrane obtained in Comparative Example 1;
[0027] Figure 4 The lithium ion conductivity diagram of the PEO-based organic-inorganic composite polymer electrolyte membrane obtained in Example 1;
[0028] Figure 5The interfacial impedance diagram of the PEO-based organic-inorganic composite polymer electrolyte membrane obtained in Example 1;
[0029] Figure 6 The lithium ion conductivity diagram of the PEO-based organic-inorganic composite polymer electrolyte membrane obtained in Example 2;
[0030] Figure 7 The interfacial impedance diagram of the PEO-based organic-inorganic composite polymer electrolyte membrane obtained in Example 2;
[0031] Figure 8 The lithium ion conductivity diagram of the PEO-based organic-inorganic composite polymer electrolyte membrane obtained in Example 3;
[0032] Fig. 9 The interfacial impedance diagram of the PEO-based organic-inorganic composite polymer electrolyte membrane obtained in Example 3;
[0033] Fig.10 The lithium ion conductivity diagram of the PEO-based organic-inorganic composite polymer electrolyte membrane obtained in Example 4;
[0034] Fig.11 The interfacial impedance diagram of the PEO-based organic-inorganic composite polymer electrolyte membrane obtained in Example 4;
[0035] Fig.12 The lithium ion conductivity diagram of the PEO-based organic-inorganic composite polymer electrolyte membrane obtained in Example 5;
[0036] Fig.13 The interfacial impedance diagram of the PEO-based organic-inorganic composite polymer electrolyte membrane obtained in Example 5;
[0037] Fig.14 This is a test diagram of the cycle performance of a full battery of the PEO-based organic-inorganic composite polymer electrolyte membrane obtained in Example 5;
[0038] Fig.15 The lithium ion conductivity diagram of the PEO-based organic-inorganic composite polymer electrolyte membrane obtained in Comparative Example 2;
[0039] Fig.16 This is the interfacial impedance diagram of the PEO-based organic-inorganic composite polymer electrolyte membrane obtained in Comparative Example 2. DETAILED DESCRIPTION
[0040] The present invention is described in detail below in conjunction with specific embodiments. It should be noted that the following embodiments are only further descriptions of the present invention, but the protection scope of the present invention is not limited to the following embodiments.
[0041] In the following examples, the raw materials, reagents and equipment used can be obtained from commercial sources or by existing known methods unless otherwise specified. The number average molecular weight of PEO is 600,000. Before use, PEO was vacuum dried at 45°C for 12 hours to remove moisture.
[0042] The lithium ion conductivity and interface impedance were tested using an electrochemical workstation at room temperature (25°C). The battery cycle performance was tested using a battery charge and discharge tester at room temperature (25°C).
[0043] Example 1
[0044] A method for preparing an organic-inorganic composite polymer solid electrolyte is as follows:
[0045] At a molar ratio of EO:Li=16:1, 6.72g PEO and 2.87g LiTFSI were weighed, and then 4.795g LLZTO powder and 1.918g 2-pyrazine amidine hydrochloride were added. Acetonitrile was added as a solvent, and the mixture was heated and stirred at 20°C for 12h to obtain a uniformly mixed slurry, which was then cast in a polytetrafluoroethylene mold and vacuum dried at 60°C for 24h to obtain a PEO-based organic-inorganic composite polymer electrolyte membrane. After cutting, its lithium ion conductivity was tested, and its lithium ion conductivity was 3.6×10 - 4 S / cm( Figure 4 ), the interface impedance is 113.2Ω( Figure 5 ), and its elastic modulus was tested to be 2.2MPa.
[0046] It can be seen from Example 1 and Comparative Example 1 that the addition of 2-pyrazine amidine hydrochloride effectively improves the lithium ion conductivity and mechanical strength of the solid-state battery, and also improves the interface performance.
[0047] Example 2
[0048] A method for preparing an organic-inorganic composite polymer solid electrolyte is as follows:
[0049] 3.36g PEO and 1.435g LiBOB were weighed at a molar ratio of EO:Li=16:1, and then 0.12g Li3InCl6 powder and 1.59g 2-pyrazine amidine hydrochloride were added. NMP was added as a solvent, and the mixture was heated and stirred at 30°C for 10h to obtain a uniformly mixed slurry, which was then cast in a polytetrafluoroethylene mold and vacuum dried at 80°C for 10h to obtain an organic-inorganic composite polymer electrolyte membrane. After cutting, its lithium ion conductivity was tested, and its lithium ion conductivity was 3.9×10 -4 S / cm( Figure 6 ), the interface impedance is 162.5Ω( Figure 7), and its elastic modulus was tested to be 2.4MPa.
[0050] Example 3
[0051] A method for preparing an organic-inorganic composite polymer solid electrolyte is as follows:
[0052] 12.6 g PEO and 1.87 g LiFSI were weighed at a molar ratio of EO:Li=30:1, and then 1.447 g LATP powder and 0.965 g N-hydroxy-6-chloroindolecarboxamidine were added. DMAC was added as a solvent, and the mixture was heated and stirred at 60 °C for 18 h to obtain a uniformly mixed slurry, which was then cast in a polytetrafluoroethylene mold and vacuum dried at 60 °C for 36 h to obtain an organic-inorganic composite polymer electrolyte membrane. After cutting, its lithium ion conductivity was tested, and its lithium ion conductivity was 5.7×10 -4 S / cm( Figure 8 ), the interface impedance is 241.5Ω( Fig. 9 ), and its elastic modulus was tested to be 2.8MPa.
[0053] Example 4
[0054] A method for preparing an organic-inorganic composite polymer solid electrolyte is as follows:
[0055] 1.68g PEO and 1.52g LiPF6 were weighed at a molar ratio of EO:Li = 4:1, and then 0.1144g LAGP powder and 1.716g methyl-[5-(N-methyl-N-phenylamino)-2,4-pentadienyl]phenylammonium chloride were added. NMP was added as a solvent, and the mixture was heated and stirred at 80°C for 24h to obtain a uniformly mixed slurry, which was then cast in a polytetrafluoroethylene mold and vacuum dried at 90°C for 8h to obtain an organic-inorganic composite polymer electrolyte membrane. After cutting, its lithium ion conductivity was tested, and its lithium ion conductivity was 6.6×10 -4 S / cm( Fig.10 ), the interface impedance is 113.2Ω( Fig.11 ), and its elastic modulus was tested to be 3.4MPa.
[0056] Example 5
[0057] A method for preparing an organic-inorganic composite polymer solid electrolyte is as follows:
[0058] 3.36g PEO and 1.06g LiODFB were weighed at a molar ratio of EO:Li=8:1, and then 0.442g LSPCl powder and 0.663g 4-methylsulfonylphenylamidine were added. NMP was added as a solvent, and the mixture was heated and stirred at 80°C for 24h to obtain a uniformly mixed slurry, which was then cast in a polytetrafluoroethylene mold and vacuum dried at 100°C for 8h to obtain an organic-inorganic composite polymer electrolyte membrane. After cutting, its lithium ion conductivity was tested, and its lithium ion conductivity was 8.1×10 -4 S / cm( Fig.12 ), the interface impedance is 92.4Ω( Fig.13 ), and its elastic modulus is 4.2MPa. After 100 cycles at 0.5C, the discharge capacity can reach 145mAh / g, and the capacity retention rate is close to 100% ( Fig.14 ).
[0059] Comparative Example 1
[0060] A method for preparing an organic-inorganic composite polymer solid electrolyte is as follows:
[0061] The molar ratio of EO:Li=16:1, 6.72g PEO and 2.87g LiTFSI were weighed respectively, and then 0.959g LLZTO powder was added. Acetonitrile was added as a solvent, and the mixture was heated and stirred at 20°C for 12h to obtain a uniformly mixed slurry, which was then cast in a polytetrafluoroethylene mold and vacuum dried at 60°C for 24h to obtain a PEO-based organic-inorganic composite polymer electrolyte membrane. After cutting, its lithium ion conductivity was tested, and its lithium ion conductivity was 2.1×10 -6 S / cm( Figure 1 ), the interface impedance is 829.5Ω( Figure 2 ), and its elastic modulus was tested to be 1.2MPa. After 40 cycles at 0.5C, the capacity was basically reduced to 0 ( Figure 3 ).
[0062] Comparative Example 2
[0063] 6.72 PEO and 2.87 LiTFSI were weighed at a molar ratio of EO:Li = 16:1, and then 0.95 LLZTO powder and 0.1918 DBU were added. Acetonitrile was added as a solvent, and the mixture was heated and stirred at 20 °C for 12 h to obtain a uniformly mixed slurry, which was then cast in a polytetrafluoroethylene mold and vacuum dried at 60 °C for 24 h to obtain an organic-inorganic composite polymer electrolyte membrane. After cutting, its lithium ion conductivity was tested, 8.2×10 -6 S / cm( Fig.15 ), the interface impedance is 350.2Ω( Fig.16 ), and its elastic modulus was tested to be 1.8MPa.
[0064] The above-mentioned embodiments only express several implementation methods of the present invention, and the description thereof is relatively specific and detailed, but it cannot be understood as limiting the scope of the patent of the present invention. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, which all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.
Claims
1. An organic-inorganic composite polymer solid electrolyte, characterized in that: The invention comprises polyethylene oxide, lithium salt, active filler and organic additive, wherein the organic additive is an amidine compound, and the amidine compound contains one or more of halogen, phenyl, nitro, naphthyl or thiophene groups; the polyethylene oxide and the lithium salt have a molar ratio of EO:Li of (4-30):1, the total mass of the polyethylene oxide and the lithium salt has a mass ratio of (2-40):1 to the active filler, and the total mass of the polyethylene oxide and the lithium salt has a mass ratio of (1.5-15):1 to the organic additive.
2. The organic-inorganic composite polymer solid electrolyte according to claim 1, characterized in that: The amidine compound includes one or more of 3,4-dimethylbenzamide, 2-(4-fluorophenylmethylsulfonyl)hydroxyacetamidine, 2-pyrazineamidine hydrochloride, N-hydroxy-6-chloroindoleacetamidine, N-[3-(aminomethyl)benzyl]acetamidine, methyl-[5-(N-methyl-N-phenylamino)-2,4-pentadienyl]phenylammonium chloride, esifamidine, pentafluoropropylamidine, N'-hydroxy-2-naphthamide, heptafluorobutyrylamidine, 2-(2-thienyl)hydroxyacetamidine, propamidine, 4-methylsulfonylbenzamide, 2-N-BOCaminoethylamidine, 4-benzylpiperazine-1-carbonamidine, and 4-nitrobenzamide.
3. The organic-inorganic composite polymer solid electrolyte according to claim 1, characterized in that: The amidine compound is selected from at least one of 2-pyrazine amidine hydrochloride, N-hydroxy-6-chloroindole carboxamidine, methyl-[5-(N-methyl-N-phenylamino)-2,4-pentadienyl]phenylammonium chloride and 4-methylsulfonylbenzene amidine.
4. The organic-inorganic composite polymer solid electrolyte according to claim 1, characterized in that: The lithium salt includes one or more of LiFSI, LiTFSI, LiBOB, LiODFB, LiPF6, LiClO4, and LiNO3.
5. The organic-inorganic composite polymer solid electrolyte according to claim 1, characterized in that: The active filler includes one or more of lithium lanthanum zirconium tantalum oxide, lithium indium chloride, lithium aluminum titanium phosphide, lithium aluminum germanium phosphide and lithium phosphorus sulfur chlorine.
6. The organic-inorganic composite polymer solid electrolyte according to claim 1, characterized in that: The molar ratio of EO:Li of the polyethylene oxide and the lithium salt is (7-9):1, the mass ratio of the total mass of the polyethylene oxide and the lithium salt to the active filler is (9-11):1, and the mass ratio of the total mass of the polyethylene oxide and the lithium salt to the organic additive is (6-7):
1.
7. The method for preparing the organic-inorganic composite polymer solid electrolyte according to any one of claims 1 to 6, characterized in that: The method comprises the following steps: weighing each component, adding an organic solvent, heating and stirring to obtain a uniformly mixed slurry, and then casting and vacuum drying to obtain a polymer solid electrolyte.
8. The preparation method according to claim 7, characterized in that: The organic solvent comprises one or more of acetonitrile, dimethylacetamide, dimethyl sulfoxide, N-methylpyrrolidone and N,N-dimethylformamide; the temperature for heating and stirring is 20-150°C and the time is 8-60h; the temperature for vacuum drying is 20-100°C and the time is 2-48h.
9. The preparation method according to claim 8, characterized in that: The temperature used for heating and stirring is 20-80°C and the time is 10-24 hours; the temperature used for vacuum drying is 60-100°C and the time is 8-36 hours.
10. Use of the organic-inorganic composite polymer solid electrolyte according to any one of claims 1 to 6 or the organic-inorganic composite polymer solid electrolyte prepared by the method according to any one of claims 7 to 9 in preparing a lithium electronic battery.
Citation Information
Patent Citations
Ionic plastic crystals, compositions comprising same, methods of making same and uses thereof
CN116806221A
Organic-inorganic composite polymer solid electrolyte as well as preparation method and application thereof
CN117352833A
Electrolyte for secondary lithium battery and secondary lithium battery using the same
CN103811813A
Organic-inorganic co-modified PEO solid electrolyte and preparation method thereof
CN117525574A
Solid electrolyte composition, solid electrolyte sheet for all-solid type secondary battery, electrode sheet for all-solid type secondary battery, all-solid type secondary battery, and method for manufacturing branched polymer
JP2017130264A